Improving the Managerial Performance of School Principals Through a Directive and Collaborative Approach - Setiyo, Setiyo; Hadiati, Eti (Universitas Islam Negeri Raden Intan Lampung, 2024)
The problems found are positive, namely that the researcher wants to know more comprehensively about efforts to improve the managerial performance of school principals through a directive and collaborative approach at SMK Negeri 1 Bandar Lampung, SMK Negeri 4 Bandar Lampung and SMK Negeri 2 Kalianda in the odd semester of the 2021/2022 academic year so that The researcher aims to analyze the Managerial Performance of School Principals Using a Directive and Collaborative Approach at SMK Negeri 1 Bandar Lampung, SMK Negeri 4 Bandar Lampung and SMK Negeri 2 Kalianda in the Odd Semester of the 2021/2022 Academic Year. The data above was found through qualitative field research methods. Investigation of deductive as well as inductive reasoning processes, and dynamic analysis of ties between observable events, are emphasized in qualitative research. The results of the research show that there is a significant influence between motivation on teacher performance at SMK Negeri 1 Bandar Lampung, SMK Negeri 4 Bandar Lampung and SMK Negeri 2 Kalianda, so that hypothesis 2 is accepted, Managerial Supervision Guidelines for Implementing Duties of School/Madrasah Supervisors (Directorate of Educational Personnel, 2009 : 20) states that managerial supervision is supervision relating to aspects of school management that are directly related to increasing school efficiency and effectiveness which includes planning, coordination, implementation, assessment, development of educational human resource (HR) competencies and other resources. In carrying out managerial functions, school/madrasah supervisors act as: 1) collaborators and negotiators in the process of planning, coordinating and developing school management 2) assessors in identifying weaknesses and analyzing school potential 3) information centers for school quality development 4) evaluators of the meaning of supervision results . Managerial supervision focuses on observing aspects of school management and administration which function as supporting the implementation of learning